Androgen Receptor in Breast Cancer: From Bench to Bedside - Chen, Mengyao; Yang, Yunben; Xu, Kai; Li, Lili; Huang, Jian; Qiu, Fuming (Frontiers in Endocrinology, 2020)
Breast cancer (BC) is one of the most common malignancies and the leading cause of cancer-related mortality in women. Androgen receptor (AR) is frequently expressed in diverse BC subtypes. Accumulating evidence has revealed that AR might be a predictive or prognostic factor and a drug target in BC. AR expression and AR pathways differ in various BC subtypes, thereby resulting in controversial inferences on the predictive and prognostic value of AR. Herein, we summarized the roles of AR in different BC subtypes and AR-targeting therapies based on preclinical and clinical studies. Moreover, we highlighted the possible efficacy of a combination therapy via exploiting the AR-related mechanisms and the research on therapeutic resistance.